Hubungan Manarche, Kebiasaan Olahraga, Dan Lama Menstruasi Dengan Kejadian Dismenore Primer Pada Remaja Putri Kelas X Di Sman 1 Sindangbarang Kabupaten Cianjur : The Relationship Between Menarche, Sports Habit and Menstrual Length with the Incidence of Primary Dysmenorrhea in Class X Adolescent Girls at Sman 1 Sindangbarang, Cianjur Regency - Kusuma, Widi Mulia Endar (Indonesian Scholar Journal of Nursing and Midwifery Science (ISJNMS), 2025)
Introduction: Primary dysmenorrhea is a condition that occurs due to changes in the hormone prostaglandin which is a hormone produced by the lining of the uterus. Data from the World Health Organization (WHO) in 2021 found an incidence of 1,769,425 women (90%) who experienced dysmenorrhea. In Cianjur in 2021 from regional health report data it was found that 1,07-1,31% of the number of visits to the obstetrics department were dysmenorrhea sufferers. It was reported that 30-60% of female teenagers experienced dysmenorrhea 7-15% did not go to school or work.  Methods: This research uses quantitative methods with a cross-sectional study design. The total population is 176 female students and the sample size of 64 female students using a probability sampling technique using a random sampling system.  Results: The results of statistical tests obtained p-value ​​for menarche (0.000); exercise habits (0,000); and length of menstruation (0,000); which means that H0 is rejected and it can be concluded that there is a significant relationship between manarche exercise habits and length of menstruation with the incidence of primary dysmenorrhea for young women in class X at SMAN 1 Sindangbarang, Cianjur district in 2024.  Discussion: From the results of this research there are still predisposing factors that influence the condition of dysmenorrhea and menstruation in female students apart from the factors studied such as the habit of consuming junk food, heredity and also their nutritional patterns. Suggestions from the research that has been carried out the researcher tries to provide several suggestions to future researchers. With the hope that the suggestions given can be useful in further research.